Nature-based Solutions for Urban Flooding and Drainage Management in Long Xuyen City - Quang Hung, Nguyen; Minh Dat, Phan; Van Ninh, Luu; Thi Lien, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1S, 2025)
Long Xuyen City, located in the Mekong Delta, is highly vulnerable to urban flooding due to its flat, low-lying terrain, and tidal influences. Recent climate change impacts, including heavy rainfall and sea level rise, have further intensified localized inundation. This study employed an urban hydrological model to simulate flood dynamics and assess adaptation strategies. The model was calibrated and validated using three observed rainfall events from 2021 and 2022, demonstrating reliable performance. Climate change scenarios were developed for mid-century (2046 - 2065) under both high and low emission scenarios to evaluate future risks. Nature-based solutions (NbS) were applied at four severely flooded sites, showing effective mitigation of inundation even under adverse climate conditions. The findings highlight the potential of NbS as a sustainable strategy for enhancing urban flood resilience in deltaic cities facing climate uncertainty.